The influence of the brittle-ductile transition zone on aftershock and foreshock occurrence - Giuseppe Petrillo (Nature Portfolio, 2020)
Earth surface continues to slip after large earthquakes at a slow velocity for a period of a year or more. In this study, the authors show how such slow slip before and after large earthquakes relates to the interaction of the brittle zone of the fault with the ductile zone at greater depth.